Reverse Supply Chain and Its Effect on Customer Satisfaction: A Comparative and SERVQUAL Analysis of Retail Practices - Bajah, Jeff (International Journal of Supply Chain Management, 2025)
Reverse supply chain (RSC) operations have become increasingly critical for retail firms seeking to enhance sustainability, reduce costs, and retain customer loyalty. While traditional supply chain research emphasizes forward logistics, customer satisfaction in reverse logistics remains underexplored. This study investigates the relationship between RSC processes and customer satisfaction using qualitative semi-structured interviews with six U.S.-based supply chain professionals. It applies Qualitative Comparative Analysis (QCA) and the SERVQUAL model to analyze the configurations of RSC conditions that influence customer experience. Four key drivers emerged: return process efficiency, communication and transparency, employee competence, and alignment with customer expectations. A truth table developed using fuzzy set QCA 3.0 reveals five RSC condition combinations that consistently lead to high satisfaction. Customer communication and a hasslefree return process were necessary in all successful configurations. This study highlights best practices, including flexible return options, use of return metrics, staff training, and clear return policies. It contributes to the existing literature by reconceptualizing the reverse supply chain as not merely a cost recovery or operational function, but as a strategic service platform for generating competitive advantage in retail logistics. Further, this research offers a novel analytical framework capable of identifying multiple high-performance pathways rather than prescribing a one-size-fits-all solution. The emphasis on equifinality, or the possibility of different configurations leading to the same positive outcome, reflects the complexity and diversity of modern supply chain environments and aligns with the contemporary demands of supply chain managers.